(untitled) (Research, Society and Development, 2020)
Parendodontic surgery presents itself as a therapeutic alternative that can be performed when conventional endodontic retreatment is not possible, with the purpose of solving problems involved in apical injuries, aiming to combat pathogenic agents, as in cases of calcified teeth. In this context, the objective of this work is to describe a clinical case of parendodontic surgery of tooth 13 with calcified root and a periradicular lesion. This is a descriptive study based on a case report of a 43-year-old female patient, who sought the service of the Primary Care Clinic III at the Pernambuco Dental School of the University of Pernambuco, for endodontic treatment of the element 13. After the diagnosis of periradicular injury and internal calcification of tooth 13, it was decided to perform parendodontic surgery. Antibiotic prophylaxis was performed 1 hour before the procedure, antisepsis of the region and local anesthesia. The surgical flap of choice was Neumann. The lesion was located using an endodontic file, access to the lesion, curettage, apicectomy and retrograde filling with MTA and local suture. After the surgery, a periapical radiography was performed and it was possible to verify the success of the procedure. Thus, parendodontic surgery is an indication for teeth with completely calcified roots and without the possibility of conventional endodontic treatment.